Electron energy probability function modulation with external electron beam in capacitive coupled radio frequency discharges. Issue 3 (14th November 2017) - Zhang, Ya; Huang, Jia‐long; Yi, Lin; Wang, Hong‐yu; Jiang, Wei
Abstract : We investigate the effect of external electron beam injection on plasma kinetics of a radio‐frequency (rf) capacitive argon discharge at a pressure of 100 mTorr. The rf voltage is applied to the one electrode. Monoenergetic electron beam is injected from the other electrode, with a laboratory accessible injection current and energy. The electron beam injected electrode is grounded. A direct‐implicit particle‐in‐cell/Monte‐Carlo method is used to self‐consistently simulate the plasma density, electron temperature, plasma potential, electron energy probability function (EEPF), and the electron and ion fluxes. The presence of the electron beam increases the plasma density, while decreases the electron temperature and the plasma potential. The plasma density can increase by a factor of 5, at the same time the electron temperature can decrease from 3 to 0.5 eV. The reason is that, with the electron injection, there are more low‐energy electrons occupation in the EEPF. The EEPF is sensitive to the beam modulation: even a small beam current of 0.01A can modify the EEPF significantly. This may have crucial importance for plasma processing of polymers and graphene, where low energy treatment is desired. In addition, electron and ion fluxes to the ground electrode, are also significantly modified with increasing flux and decreasing bombardment energy. Abstract : The effect of electron beam on plasma kinetics of a radio‐frequency capacitive argon discharge is investigated by a particle‐in‐cell/Monte‐Carlo method. There are more low‐energy electrons occupation in the electron energy probability function (EEPF) with the electron injection. The EEPF is sensitive to the beam modulation. The electron and ion fluxes are also modified with increasing flux and decreasing bombardment energy.